Analysis of Determinant Indonesian Tuna Fish Competitiveness in Japanese Market - Sri Hidayati; Dwidjono H. D; Masyhuri Masyhuri; Kamiso H. N (International Journal of Agriculture System, 2015)
Japan is the main market of Indonesian tuna exports, either the world’s largest tuna market, even so the competition level is high. This condition has made it as the main point for Indonesia to be able to compete it’s tuna in the global market. The research used time series data of world’s tuna’s import and export in 1982-2012 from UN Comtrade and Indonesia Ministry of Maritime Affairs and Fisheries. Data were analyzed to measure market share (MS), Revealed Symmetric Comparative Advantage (RSCA), Trade Specialist Ratio (TSR), while the determinant (factors) of competitiveness employed simultaneous equations. The results showed that: (1) The average market share of Indonesian tuna in the Japanese market was 25.20%, (2) Indonesia tuna have a high competitiveness and it growth to maturity, (3) Quality and trust is a decisive determinant (factor) of Indonesian tuna competitiveness in the Japanese market.